Media Technology, Adult Education, and National Development: The Malaysian Experience - Reybold, L. Earle (Universiti Putra Malaysia Press, 1994)
This article explores the use of media technology in Malaysia's adult education programmes within an overall national development context. A qualitative methodology incorporating non-participant observation, reportorial interviews, and archival collection of news articles, speeches, and other printed materials was used to investigate three areas of research questions: I) defining basic and functional literacy in Malaysia, 2) the role of media technology in adult education, and 3) the social impact mediated and media-enhanced educational formats on personal, social, cultural, and political development. The theoretical framework for the study includes national development models, adult literacy in developing countries, and distance education as an educational delivery system, with the analysis of the results within a neo-Modernization model of national development. Although no evidence of systematic adult basic education in Malaysia was found, there are diverse nonformal functional literacy activities for adults, many ofwhich are mediated or media-enhanced. The study questions the appropriateness of distance education techniques for teaching Malaysian adults who are no longer in the formal school system. The implications of the findings for Malaysian educators, administrators, and policymakers, and the impact of these results on national development theory are discussed.